Hybrid ultra‐HVDC system with LCC and cascaded hybrid MMC. Issue 16 (6th December 2018) - Yang, Ruizhang; Xiang, Wang; Lin, Weixing; Wen, Jinyu
Abstract : Nowadays, the hybrid high‐voltage direct current (HVDC) system consisting of line commutated converter (LCC) and modular multilevel converter (MMC) has become the most competitive candidate in multi‐infeed power systems. Owing to the limitation of insulated‐gate bipolar transistor's withstand voltage, the DC voltage rating of MMC is not compatible with the LCC valve. To increase the DC voltage level, the number of sub‐modules of each arm should be increased drastically, leading to many technical problems in communication design, optical fibre instalment, cooler system design and so on. To overcome the above problems, a hybrid HVDC system consisting of LCC and cascaded hybrid MMC valves is proposed to realise ultra‐HVDC transmission. It can switch two operating modes (single valve/double valve) according to the conditions so that the system can maintain a certain power transmission when one of the valves quit operation during faults or maintenances. Meanwhile, by implementing the hybrid MMC, the system can ride through DC faults. The design of the topology and controllers, the DC fault ride‐through strategy and the online switching strategy for MMCs will be presented in this study. Finally, the performance during DC faults and online switching is verified by extensive simulations.